Analisis Layanan Website Perusahaan Leasing Mobil Menggunakan Metode Webqual 4.0 - Garry Briyant Rosario; Bertalya Bertalya (Jurnal Indonesia Sosial Teknologi, 2023)
Technological developments in this era have grown rapidly, especially in the field of the internet. As internet users increase in the world, it makes it easier for business people to market and develop their business land so that consumers can choose goods or services as efficiently as possible. Sharing buying and selling transactions is now very easy and internet buying and selling transactions are often carried out via the internet, this is called e-commerce. The high growth of e-commerce and intense competition requires online business people to improve the quality of the online business website to increase website user satisfaction in order to win the competition. User satisfaction is influenced by usability, information quality, and service interaction quality. The car leasing company is an e-commerce business based on the Business to Business (B2B) marketplace. The purpose of this research is to analyze the effect of website quality (Webqual) on user satisfaction using a sample of 100 respondents. The method used in this research is descriptive analysis. This study uses SPSS 2.2 in data processing. Based on the results of data analysis, it was found that the variables consisting of usability, information quality, and service interaction quality from the rating scale illustrate the rating of the leasing company's website to get a good rating.